DETERMINAN REPURCHASE INTENTION KONSUMEN PRODUK FASHION PADA TIKTOK LIVE STREAM - Viky Effendi; Usep Suhud; Shandy Aditya (Digital Business Journal, 2023)
ABSTRAKThis study aims to analyze the factors that determine the repurchase intention of consumers of fashion products on TikTok live stream using variables service quality, customer satisfaction, and customer trust. The method of data collection using questionnaires distributed online to 251 respondents. The criteria for respondents in this study are TikTok application users who are domiciled in Greater Jakarta, are at least 17 years old, and have made purchases on TikTok live stream Erigo at least twice in the last six months. Data were processed using software analysis techniques SPSS and SEM AMOS. The results showed that service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer trust, customer satisfaction has a positive and significant effect on customer trust, customer satisfaction has a positive and significant effect on repurchase intention, and customer trust has a positive and significant effect on repurchase intention. Keyword: repurchase intention, customer satisfaction, customer trust, service quality, TikTok live stream. ABSTRAKPenelitian ini bertujuan untuk menganalisis faktor-faktor yang menentukan repurchase intention konsumen produk fashion pada TikTok live stream dengan menggunakan variabel service quality, customer satisfaction, dan customer trust. Metode pengumpulan data menggunakan kuesioner yang disebarkan secara daring kepada 251 responden. Kriteria responden dalam penelitian ini yaitu pengguna aplikasi TikTok yang berdomisili di Jabodetabek, berusia minimal 17 tahun, dan sudah pernah melakukan pembelian di TikTok live stream Erigo minimal dua kali dalam kurun waktu enam bulan terakhir. Data diolah dengan menggunakan teknik analisis software SPSS dan SEM AMOS. Hasil penelitian menunjukkan bahwa service quality berpengaruh positif dan signifikan terhadap customer satisfaction, service quality berpengaruh positif dan signifikan terhadap customer trust, customer satisfaction berpengaruh positif dan signifikan terhadap customer trust, customer satisfaction berpengaruh positif dan signifikan terhadap repurchase intention, dan customer trust berpengaruh positif dan signifikan terhadap repurchase intention. Kata Kunci: repurchase intention, customer satisfaction, customer trust, service quality, TikTok live stream